2018
DOI: 10.37333/001c.7022
|View full text |Cite
|
Sign up to set email alerts
|

Nature, Benefits, Challenges and Opportunities of University-Community Engagement: In the Case of University of Gondar, Ethiopia

Abstract: The relationship that exists between universities and local communities ultimately influences the growth and development of both entities in either constructive or undesirable ways. The study discussed in this article examined the nature, benefits, challenges, and opportunities of universitycommunity engagement (UCE) at the University of Gondar in Ethiopia. The study employed a descriptive qualitative research design. Specifically, the researchers utilized a purposive sampling technique to select participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(12 reference statements)
1
0
0
Order By: Relevance
“…In his finding, Mekango (2013) stressed that financial constraints are challenges to developing partnerships in Ethiopia. The findings also conform to Desta and Belay (2018) who indicated that a lack of resources (financial and human) is considered a challenge.…”
Section: 90supporting
confidence: 85%
“…In his finding, Mekango (2013) stressed that financial constraints are challenges to developing partnerships in Ethiopia. The findings also conform to Desta and Belay (2018) who indicated that a lack of resources (financial and human) is considered a challenge.…”
Section: 90supporting
confidence: 85%